Pengembangan Aplikasi Pembelajaran Berbasis Android Materi Geometri Fase A Kurkulum Merdeka - Henry Zazin Afidin; Nursiwi Nugraheni (Pendagogia: Jurnal Pendidikan Dasar, 2024)
This research aims to develop learning media based on android applications, which can be used as a support for learning geometry material phase A Kurikulum Merdeka. The learning media created combines the concept of learning and practicing directly. Where through this media students can interact directly with the material. The achievements of this research: (1) Developing android-based learning media products that can be used as a means of supporting learning. (2) Knowing the process of developing android applications that are in accordance with the geometry material phase a independent curriculum. (3) Knowing the impact of the implementation of android-based geometry learning media on student learning outcomes. The test subjects in this study were second grade students of SD Negeri 2 Sokaraja. The model used in this research is the Plomp & Nieveen (2010) development model. The result of this research is an android-based learning media named as "shape safari". This media gets validation results from material experts with a percentage of 81%. Then get validation results from media experts of 73%. Then from the results of the trial on the research subjects, this media can improve the understanding of students as evidenced by the increase in the final results of students in the questionnaire. Where the use of this media is able to increase the value of the questionnaire from an average of 12 points to an average of 17 points.